Shaking Table Tests on 1/4 Scaled Shapeless Stone Masonry Houses with and without Retrofit by Polypropylene Band Meshes - Meguro, K.; Sathiparan, N.; Sakurai, K.; Numada, M. (My University, 2012)
We have developed a technically feasible and economically affordable retrofitting method using Polypropylene band (PP-band) for low earthquake resistant masonry structures in developing countries (Mayorca and Meguro, 2004). And we have done many experimental and numerical researches on the effects of the PP-band method on the dynamic behavior of brick and adobe, unburned clay brick, masonry houses. Results of the material tests and shaking table tests using building models show that the PP-band retrofitting method can enhance safety of both existing and new brick and adobe masonry buildings even in worst case scenario of earthquake ground motion. However, the effects of the method on stone masonry houses, especially made of shapeless stones were not checked well yet. Therefore, in this study, as an extension of application of PP-band retrofitting method, we have carried out diagonal shear tests and shaking table tests using PP-band retrofitted and non-retrofitted stone masonry models made of shapeless stones. From the results obtained, it can be concluded that stone masonry made of shapeless stones can be retrofitted well with PP-band method and the method can be one of the optimum solutions for promoting safer building construction in developing countries and contribute earthquake disaster mitigation in the future.
Keywords: Stone masonry; masonry structure